2017
DOI: 10.1016/j.jid.2017.02.432
|View full text |Cite
|
Sign up to set email alerts
|

413 Formulation with low pH decreases skin pH, restores disrupted epidermal barrier and improves lipid lamellae structure

Abstract: RNA-protein interactions play critical roles in diverse cellular functions and their perturbations may contribute to human disease. A synonymous single nucleotide polymorphism (SNP) in the coding sequence of corneodesmosin (CDSN), a gene essential for normal epidermal differentiation whose mutation leads to peeling skin syndrome, has long been linked to psoriasis in diverse ethnic groups. How the psoriasis-associated CDSN variant might contribute to disease pathogenesis, however, is unclear. To address this, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As the stratum corneum is constructed predominantly of keratinocytes, many studies have demonstrated that the acidic microenvironment of the skin milieu plays a key role in keratinocyte differentiation, especially during wound repair. Keratinocytes differentiation triggers an upregulation of ceramides synthesis, lipids, and aids in the restoration of lipid lamellae structure which are required to restore the epidermal layer [ 40 , 41 , 42 ]. Thus, this helps to explain the observed faster re-epithelization of the epidermal layer by once-daily phosphoric acid treatment at pH 4 (PA4-1), with contrasting slower internal tissue recovery.…”
Section: Discussionmentioning
confidence: 99%
“…As the stratum corneum is constructed predominantly of keratinocytes, many studies have demonstrated that the acidic microenvironment of the skin milieu plays a key role in keratinocyte differentiation, especially during wound repair. Keratinocytes differentiation triggers an upregulation of ceramides synthesis, lipids, and aids in the restoration of lipid lamellae structure which are required to restore the epidermal layer [ 40 , 41 , 42 ]. Thus, this helps to explain the observed faster re-epithelization of the epidermal layer by once-daily phosphoric acid treatment at pH 4 (PA4-1), with contrasting slower internal tissue recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Skin care products adjusted to pH 4 have been used successfully in acne skin . These products improve the physiological microbial flora, skin barrier and lipid lamellae structure, reduce skin dryness and have been described to be more favorable compared with formulations with a pH of 5.8–6.0 . Newborn and aged skin exhibit an increased SC pH, too.…”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
“…Daily use of moisturizers on newborns and infants with an impaired skin barrier and increased SC pH is helpful in preventing the atopic march . A glycolic acid‐containing moisturizer with pH 4 reduces the SC pH in healthy, elderly and diabetic subjects, possibly by influencing cathepsin D‐like and chymotrypsin‐like proteinases …”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
See 2 more Smart Citations